An Approach towards the Synthesis of the Spiroimine Fragment of 13‐Desmethylspirolide C and Gymnodimine A. Issue 6 (2nd January 2019) - Guthertz, Alexandre; Lusseau, Jonathan; Desvergnes, Valérie; Massip, Stéphane; Landais, Yannick
Abstract: A general access to the spiroimine skeleton of gymnodimine and spirolides is described, relying on the construction of the cyclohexene fragment using an enantiocontrolled Diels–Alder reaction, the installation of the all‐carbon quaternary stereocenter through a stereocontrolled alkylation or aldolisation and the elaboration of the lateral chains at C7 and C22 using Wittig–Horner olefinations. The spiroimine core of gymnodimine is made available through a 16‐step linear sequence in a 21 % overall yield. Abstract : All‐carbon stereocenter : A synthesis of the spiroimine skeleton of gymnodimine and spirolides is described that relies on the construction of the cyclohexene fragment using an enantiocontrolled Diels–Alder reaction, the installation of the all‐carbon quaternary stereocenter center through alkylation or aldolization and the elaboration of lateral chains using Wittig–Horner olefinations. The spiroimine core of gymnodimine is accessible through a 16‐step linear sequence and a 21 % overall yield.